Evaluation of an in-house polymerase chain reaction for detection of Neisseria gonorrhoeae in urogenital samples. Issue 6 (1st June 1999) - Roymans, R; Onland, G; Jansz, A; Quint, W; Boel, E
Abstract : AIM: To develop and evaluate a one day in-house polymerase chain reaction (PCR) assay for the detection of Neisseria gonorrhoeae DNA in urogenital samples. METHODS: 429 urogenital specimens were tested for the presence of N gonorrhoeae by in-house PCR and by Gen-Probe. The PCR assay amplifies target sequences within the N gonorrhoeae cppB gene on the 4.2 kb cryptic plasmid, after which amplicons are detected by a streptavidinbiotin based enzyme immunoassay using an internal probe. Discordant specimens were further evaluated by repeating the PCR and the Gen-Probe assay, and by an additional PCR using another set of 16S primers followed by radioactive detection of amplicons on a Southern blot. RESULTS: Of the 429 samples tested, 15 were found positive by in-house PCR, eight of which were confirmed by Gen-Probe. Of the seven discrepant samples, five were confirmed by 16S PCR and are also considered true positive. The remaining two samples were positive in the in-house PCR only, and are considered false positive. After resolution of discrepant samples, the sensitivities of the N gonorrhoeae assays were 100% and 61.5% for the in-house PCR and Gen-Probe, respectively, while specificities were comparable at 99.5% and 100%. CONCLUSIONS: The in-house PCR for the detection of N gonorrhoeae DNA is at least comparable to Gen-Probe in performance. An extended evaluation period should elucidate if the additional five GO-PCR positive specimens, confirmed by 16S PCR, are caused by persistence of DNA or whether the method is indeed more sensitive.